2000
DOI: 10.1115/1.1287270
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of a Smooth Circular Cylinder Oscillating Normal to a Uniform Flow

Abstract: Results of a numerical evaluation of transitional flow around a circular cylinder forced to oscillate in a direction normal to a uniform flow are presented. The cylinder is considered to be a representative of a single riser exposed to a steady current. Numerical simulations were carried out using the LES method in 2-D and 3-D with a near-wall approach that was developed without using a “law of the wall” for a finite element code (FEM). The 3-D simulations were compared with the 2-D results and experimental da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…However, it is stated by (Sarpkaya, 2004) that a greater understanding about the wake -boundary layer interaction will be achieved by simulating VIV with LES and DNS. 2D and 3D simulations of VIV were made by (Tutar & Holdo, 2000) to investigate the vortex structure formed behind a smooth circular cylinder at = 24000. A hybrid RANS-LES method named as Detached Eddy Simulation (DES) was used to solve for 3D simulation of VIV of a circular cylinder by (Saltara, D'Agostini Neto, & Lopez, 2011)at = 10000.…”
Section: Dns Allows a Direct Solution Of Navier-stokesmentioning
confidence: 99%
“…However, it is stated by (Sarpkaya, 2004) that a greater understanding about the wake -boundary layer interaction will be achieved by simulating VIV with LES and DNS. 2D and 3D simulations of VIV were made by (Tutar & Holdo, 2000) to investigate the vortex structure formed behind a smooth circular cylinder at = 24000. A hybrid RANS-LES method named as Detached Eddy Simulation (DES) was used to solve for 3D simulation of VIV of a circular cylinder by (Saltara, D'Agostini Neto, & Lopez, 2011)at = 10000.…”
Section: Dns Allows a Direct Solution Of Navier-stokesmentioning
confidence: 99%
“…The immediate concern with a 2D simulation is the assumption of two-dimensionality. Most 2D codes over-predict the drag coefficient for large Reynolds numbers by 5-10% [11] and the results from 3D codes provide better agreement with experimental data (confirmed by [9]). Reference [11] argue that a 2D simulation has its merits since the lift and drag coefficients are predicted more accurately when VIV begins, because at this point, the wake correlation length increases and the 3D influence of vortex shedding is diminished.…”
Section: B Moving Cylindersmentioning
confidence: 79%
“…It would seem then, that for the immediate future, the simulation of vortex induced vibrations can best be accomplished using large eddy simulation, and this is the focus of the work outlined in this section. Reference [9] investigated the benefits of 3D simulation using a 2D and 3D sub-grid scale LES model. They forced a cylinder to oscillate in the transverse direction at A y /D = 0.11, Re = 2.4x10 4 , and V r = 5.4 (where A y is the amplitude of motion in the transverse direction, D is the cylinder diameter, and V r is the reduced velocity) and compared the results.…”
Section: B Moving Cylindersmentioning
confidence: 99%
“…Their numerical results showed good agreement with the observation from experimental results of Feng (1968). Tutar and holdo (2000) used LES model in conjunction with the finite element method for a cylinder subjected to forced oscillation at Re= 4 2 10 × and found that three-dimensional representation is necessary to obtain accurate results. Michelassi, et al (2003) stated that LES is able to provide a much deeper insight in the wake-boundary layer interaction mechanism when comparing to two-dimensional unsteady RANS simulations.…”
Section: Turbulence Modelmentioning
confidence: 99%